2002
DOI: 10.1034/j.1600-0528.2002.00012.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental diseases in subjects with β‐thalassemia major

Abstract: Thalassemia beta major is a hereditary hemolytic anemia disease with various grades of severity, which can be found with no or less globin chain qualitative synthesis. The patient often experiences hepatosplenomegaly, growth retardation and bone disorder and the thalassemia facies/chipmunk face appearance. The orofacial manifestations of beta thalassemia major are prominent cheek bones and protrusive premaxillae due to erythroid hyperplasia with depressed bridge of the nose. The dentition shows protrusion, fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
2
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 12 publications
3
36
2
2
Order By: Relevance
“…Periodontitis represents a potential source of inflammation, and during the formation of peridontal pockets colonized with gramnegative anaerobic bacteria, an inflammatory cell infiltrate is recruited into the lesion that secretes proinflammatory mediators (41,46). Both gingivitis and periodontitis are seen more frequently in ESRD patients (47)(48)(49). Gingival hyperplasia is a relatively common periodontal complication in renal transplantation patients that has been attributed to cyclosporin dosage and the presence of dental plaques, likely contributing to gingival inflammation (50).…”
Section: Poor Oral Health As a Source Of Inflammationmentioning
confidence: 99%
“…Periodontitis represents a potential source of inflammation, and during the formation of peridontal pockets colonized with gramnegative anaerobic bacteria, an inflammatory cell infiltrate is recruited into the lesion that secretes proinflammatory mediators (41,46). Both gingivitis and periodontitis are seen more frequently in ESRD patients (47)(48)(49). Gingival hyperplasia is a relatively common periodontal complication in renal transplantation patients that has been attributed to cyclosporin dosage and the presence of dental plaques, likely contributing to gingival inflammation (50).…”
Section: Poor Oral Health As a Source Of Inflammationmentioning
confidence: 99%
“…4 Previous studies have reported a higher frequency of periodontal diseases and dental caries in thalassemia patients. 5 A child's oral health can have a profound impact on eating, smiling, speaking and socializing. Oral conditions; such as dental caries may result in pain.…”
Section: Introductionmentioning
confidence: 99%
“…1 It is a disease which not only affects patients but also leaves a devastating psychosocial effect on patients' family. 1 In Southeast Asia, α-thalassaemia, β-thalassaemia, hemoglobin E (Hb E) and Hemoglobin Constant Spring (Hb CS) are prevalent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thalassemias are a diverse group of genetic blood diseases characterized by absence or decreased production of either α or β-globulin protein chains, resulting in microcytic anemia of varying degrees and referred to as α or β-thalassemia [1].…”
Section: Introductionmentioning
confidence: 99%